2012
DOI: 10.1002/chem.201203129
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Hyper‐cross‐linked Polymer Monolithic Column and Its Application to the Sensitive Determination of Genomic DNA Methylation

Abstract: A hyper-cross-linked polymer monolithic column, poly(methacrylatoethyl trimethyl ammonium-co-vinylbenzene chloride-co-divinylbenzene) (MATE-co-VBC-co-DVB) with phenyl and quaternary ammonium groups was successfully prepared in the current study. The prepared monolith possesses large specific surface area, narrow mesopore size distribution and high column efficiency. The poly(MATE-co-VBC-co-DVB) monolithic column was demonstrated to have strong anion exchange/reversed-phase (SAX/RP) mixed-mode retention for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In addition, the continuous monolithic matrix was obtained and attached well to the inner wall of the monolithic column (Figure 2B) with through-pores of approximate 1.5 µm (Figure 2C). The distribution of mesopore in the poly(META- co -DVB- co -EDMA) monolith ranges from 3.3 to 4.0 nm, and the specific surface area is 426 m 2 /g (Figure 2D), which is comparable to the hypercrosslinked monolithic column [38], [39], [40].…”
Section: Resultsmentioning
confidence: 84%
“…In addition, the continuous monolithic matrix was obtained and attached well to the inner wall of the monolithic column (Figure 2B) with through-pores of approximate 1.5 µm (Figure 2C). The distribution of mesopore in the poly(META- co -DVB- co -EDMA) monolith ranges from 3.3 to 4.0 nm, and the specific surface area is 426 m 2 /g (Figure 2D), which is comparable to the hypercrosslinked monolithic column [38], [39], [40].…”
Section: Resultsmentioning
confidence: 84%
“…Binary porogen consist of 1-propanol and 1,4-butanediol was selected since they could perfectly homogenize polymer solution of MATE, VBC, and EDMA. The ratio of MATE : VBC was adopted from Chen and coworkers [33]. Each variation of the polymerization condition has significant effect on the structure of monolith.…”
Section: Results and Discussion Preparation Of Monolith Column Poly-(mmentioning
confidence: 99%
“…Poly-(MATE-co-VBC-co-EDMA) monolith was prepared by one-step thermally initiated in situ polymerization method, as described by Chen et al [33] with minor modification as shown in Fig 1. Firstly, porogen 1-propanol was mixed thoroughly with 1,4-butanediol. Subsequently, all monomers and cross-linker (MATE, VBC and EDMA) were added into porogenic solvents and mixed properly to form polymerization solution, with composition as indicated in Table 1.…”
Section: Procedures Preparation Of Monolith Column Poly-(mate-co-vbc-cmentioning
confidence: 99%
“…Poly-(MATE-co-VBC-co-EDMA) monolith was prepared by one-step thermally initiated in situ polymerization method, as described by Chen et al [33] with minor modification as shown in Fig 1. Firstly, porogen 1-propanol was mixed thoroughly with 1,4butanediol. Subsequently, all monomers and cross-linker (MATE, VBC and EDMA) were added into porogenic solvents and mixed properly to form polymerization solution, with composition as indicated in Table 1.…”
Section: Procedures Preparation Of Monolith Column Poly-(mate-co-vbc-cmentioning
confidence: 99%